Teaching Young Adults A Handbook for Teachers in Post-Compulsory Education - Dawn, Trevor; Harkin, Joe.; Turner, Gill. (Hoboken : Taylor and Francis, 2002)
Further and Higher Education in the UK has expanded greatly in recent years, bringing into education large numbers of young people who present teachers with new challenges. At the same time, there is an immense pressure to improve the quality of learning and teaching, and to encourage students to be active participants in the process. This book is aimed at teachers, aspiring teachers and other professionals in upper secondary schools, further education colleges and universities who wish to increase learner motivation and to create opportunities for greater learner autonomy. It will:* r
Preliminaries; Contents; Tables; Acknowledgements; Introduction; 1 Responding to social and technological change; 2 Developments that affect learning and teaching; 3 What is effective learning; 4 The role of students in effective learning; 5 The role of teachers in effective learning; 6 Making learning more active; 7 Developing awareness of styles of teaching; 8 The Communication Styles Questionnaire; Bibliography; Index
Description based upon print version of record.
English
Keywords: College teaching; College teaching -- Great Britain; Continuing education; Continuing education -- Great Britain; Great Britain; High school teaching; High school teaching -- Great Britain; Learning; Learning; Theory & Practice of Education; Education; Social Sciences